2020
DOI: 10.1186/s12872-020-01349-9
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review on left atrial appendage closure with the LAmbre device in patients with non-valvular atrial fibrillation

Abstract: Background: Percutaneous closure (LAAC) of the left atrial appendage (LAA) is an efficacious preventive procedure for patients with non-valvular atrial fibrillation (NVAF) and considerable bleeding risk. We sought to systematically review the available LAAC data on the novel occluder device LAmbre™. Methods: For this systematic review, a search of the literature was conducted by 3 independent reviewers, reporting the safety and therapeutic success of LAAC in patients being treated with a LAmbre™. Publications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 47 publications
(90 reference statements)
4
14
0
2
Order By: Relevance
“…The implantation success rate was generally over 96.0% with procedural guidance of TEE or ICE or fluoroscopy only for Watchman, WATCHMAN FLX, Amplatzer, and LAmbre device 7,9,16,17,26–29 . The device success was comparable for both occluders in the present study.…”
Section: Discussionsupporting
confidence: 51%
“…The implantation success rate was generally over 96.0% with procedural guidance of TEE or ICE or fluoroscopy only for Watchman, WATCHMAN FLX, Amplatzer, and LAmbre device 7,9,16,17,26–29 . The device success was comparable for both occluders in the present study.…”
Section: Discussionsupporting
confidence: 51%
“…Briefly, the LAmbre device is distinguished by achieving very high procedural success rates at 99-100%, with a low incidence of peri-procedural complications (2.9%), despite being frequently employed in patients with challenging LAA anatomies, as are shallow or multilobe LAA or those with a very wide ostium [17].…”
Section: Other Devicesmentioning
confidence: 99%
“…Barrios et al (12) pointed out that although warfarin shows a good therapeutic effect, it takes a long time to reach the ideal INR, and the maintenance time of the target range of INR is short. Ali et al's study on the recommended anti-thrombotic strategies after valve replacement suggested that patients with mechanical or biological valve replacement should use warfarin for anticoagulation after surgery, and the INR value should be maintained at 2.0-3.0 to reach anticoagulation standards (13). Therefore, in order to ensure the INR compliance rate of anticoagulation therapy, it is of great significance to analyze the factors that affect INR goal attainment.…”
Section: Discussionmentioning
confidence: 99%